Structural Characterization and Biological Activity of Polysaccharides from Stems of Houttuynia cordata - Xiaocui Liu; Jin Tian; Yinzhen Pan; Zhongqiao Li; Zhiran Zhou; Zihao Pan; Huazhang Tai; Yage Xing (Foods, 2022)
In this study, water-soluble natural polysaccharides were extracted from the stems of Houttuynia cordata Thunb (HCPS). The optimization of the hot water extraction process using response surface methodology (RSM), and the extraction factors, were analyzed by multiple stepwise regression analysis and Pearson analysis. Then, the structural characterization and biological activity of the HCPS were investigated. The results indicated that the maximum extraction yield (2.43%) of the HCPS was obtained at the optimal condition (extraction temperature for 90 °C, extraction time for 5 h, solid-liquid ratio for 1:30 g/mL). The extraction temperature was determined to be the primary factor influencing the extraction yield. The HCPS molecules had an average molecular weight of 8.854 × 103 kDa and were primarily of mannose (Man), rhamnose (Rha), glucuronic acid (GlcA), galacturonic acid (GalA), glucose (Glc), and xylose (Xyl). In addition, the backbone of the HCPS might consist of →6)-α-d-Glcp-(1→ and →6)-β-d-GalpA-(1→. The HCPS had no triple-helix structure. The scanning electron microscopy (SEM) results showed that the HCPS presented a smooth and uniform appearance, and some sheet and chain structures existed. Moreover, the HCPS exhibited significant anti-oxidant activity and inhibited the activity of α-amylase and α-glucosidase. These findings showed that HCPS might be developed into a potential material for hypoglycemia, and provides a reference for the development of Houttuynia cordata polysaccharide applications in food.